(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of study was to estimate the processing technology of soybeans produced in Latvia and to compare the possibilities of using the obtained soybean cake with imported soybean meal in the feeding of lactating sows and their offspring. From soybeans, which were processed into animal feed, we obtained a product with a high content of protein. The control group of sows and fattening pigs received the imported soybean meal mixed into the compound feed, but the trial groups compound feed was mixed with soybean cake grown and processed in Latvia. Fattening pigs were weighed regularly. Feed consumption was counted and feed conversion was calculated. Was determined meat quality, carcases weight, carcases length. The chemical composition of the manure was analysed. Statistical analysis of data was performed with SAS / STAT 9.22 software package. The inclusion of soy cakes grown and processed in Latvia in lactating sow feed increased sow milk yields traits by 3.9% at 21 day of piglet age. At the end of experiment higher live weight by 3.42% were found in the trial group. Carcass quality indicators and chemical composition of meat did not show significant differences. Was observed a tendency to decrease in manure the content of organic matter in the trial group by 3.25%, decrease levels of total phosphorus and ammonium nitrogen compared to the control group. Using soybean cakes grown and processed in Latvia is possible to develop feed rations that showed similar pig growth results to imported soybean meal.